Hyperlactemia induction modes affect the lactate minimum power and physiological responses in cycling - Zagatto, A. M.; Padulo, J.; Müller, P. T. G.; Miyagi, W. E.; Malta, E. S.; Papoti, M. (The Journal of Strength and Conditioning Research, 2014)
The aim of this study was to verify the influence of hyperlactemia and blood acidosis induction on lactate minimum intensity (LMI). Twenty recreationally trained males who were experienced in cycling (15 cyclists and 5 triathletes) participated in this study. The athletes underwent 3 lactate minimum tests on an electromagnetic cycle ergometer. The hyperlactemia induction methods used were graded exercise test (GXT), Wingate test (WAnT), and 2 consecutive Wingate tests (2 × WAnTs). The LMI at 2 × WAnTs (200.3 ± 25.8 W) was statistically higher than the LMI at GXT (187.3 ± 31.9 W) and WAnT (189.8 ± 26.0 W), with similar findings for blood lactate, oxygen uptake, and pulmonary ventilation at LMI. The venous pH after 2 × WAnTs was lower (7.04 ± 0.24) than in (p < 0.05) the GXT (7.19 ± 0.05) and WAnT (7.19 ± 0.05), whereas the blood lactate response was higher. In addition, similar findings were observed for bicarbonate concentration [HCO3] (2 × WAnTs lower than WAnT; 15.3 ± 2.6 mmol/L and 18.2 ± 2.7 mmol/L, respectively) (p < 0.05). However, the maximal aerobic power and total time measured during the incremental phase also did not differ. Therefore, we can conclude that the induction mode significantly affects pH, blood lactate, and [HCO3] and consequently they alter the LMI and physiological parameters at LMI.